The Impact of Constitutional Court Decision No. 168/PUU-XXI/2023 on The Employment Cluster in The Job Creation Law: Implications for The Use of Foreign Workers in National Strategic Projects - Estiwardani, Fitri (Jurnal Daulat Hukum, 2025)
The ratification of Law No. 11 of 2020 on Job Creation, using the omnibus law concept, marks a new beginning in the legislative process, including in the employment sectors. This law consists of 11 clusters, one of which is the Employment cluster. While the Job Creation Law has undergone changes due to judicial review, it has also faced significant debate and controversy. The omnibus concept aims to simplify, synchronize, and streamline regulations that hinder the goals of job creation and investment in the real sector. National strategic projects supported by the Job Creation Law have led to an influx of foreign workers. If the foreign worker licensing process is simplified, especially to support these national strategic projects, it must still consider that the positions filled by foreign workers cannot be filled by Indonesian workers. The debate and rejection of the Job Creation Law, culminating in the filing of a judicial review request to the Constitutional Court regarding the employment cluster (Decision 168/PUU-XXI/2023), suggests that the omnibus law concept may not be the appropriate approach for the formation of Employment Law, as there are norms that conflict with the 1945 Constitution of the Republic of Indonesia.